2015
DOI: 10.9789/2175-5361.2015.v7i1.1915-1926
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal relationships in work of multiprofessional team of family health unit

Abstract: Objective: To learn the interpersonal relationships established by the multidisciplinary team in a Family Health Unit. Method: It is a qualitative, descriptive and exploratory study in a basic health unit located in a large city in southern Rio Grande do Sul. Participants were seven professionals of the staff, whose data were collected through semi-structured interviews and then treated by thematic analysis. Results: Three themes emerged in which it was revealed the fragility of interpersonal relationships in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
0
10
0
7
Order By: Relevance
“…Factors such as individualism, lack of respect and commitment, led to a hostile interpersonal relationship. (23) One study found that having a limited number of colleagues, and negative interpersonal relationships, were significant predictors of physical violence. (24) In addition, professionals who were physically assaulted by a user of the health services interpret and attribute meanings to the relationship established with the patient for whom they provided care, and, as a consequence, these professionals developed defense mechanisms, such as affective distancing from work.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as individualism, lack of respect and commitment, led to a hostile interpersonal relationship. (23) One study found that having a limited number of colleagues, and negative interpersonal relationships, were significant predictors of physical violence. (24) In addition, professionals who were physically assaulted by a user of the health services interpret and attribute meanings to the relationship established with the patient for whom they provided care, and, as a consequence, these professionals developed defense mechanisms, such as affective distancing from work.…”
Section: Discussionmentioning
confidence: 99%
“…Interpersonal conflicts inherent in the corporate context are the main precursors of not doing teamwork, mainly because they are associated with individualism and lack of cooperation, respect, commitment and co-responsibility. On the other hand, open and transparent dialogue, respect and trust among members, the existence of spaces for discussion of ideas, conflict management and the valorization of teamwork can contribute to the maintenance of healthy interpersonal relationships and, therefore, facilitate the good development of teamwork (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Este fato corrobora estudos realizados com técnicos e auxiliares de Enfermagem, que destacaram a importância da ação coordenada da equipe de Urgência e Emergência por conseguir dar pronta resposta diante da necessidade de atendimento ao paciente. [12][13][14][15] Essas unidades de serviço possuem uma dinâmica ativa e o reconhecimento e valorização do trabalho em equipe e, constituem a principal ferramenta para tornar o processo de trabalho factível. 5,[16][17][18] Vale ressaltar que nas unidades de atendimento ao paciente crítico há escassez de tempo e de recursos e, a exigência exercida pela necessidade de assistência imediata e precisa gera um clima de tensão e conflitos intra e interpessoais.…”
Section: Métodounclassified